PATHOLOGICAL RESPONSE OF GASTRIC CANCER TO NEOADJUVANT PROLONGED CHEMORADIOTHERAPY FOLLOWED BY D2 GASTRECTOMY - Е. F. Lushnikov; А. Yu. Abrosimov; B. А. Berdov; Yu. Т. Neborak; V. Yu. Skoropad (Сибирский онкологический журнал)
Pathological response of locally advanced gastric cancer to neoadjuvant prolonged chemoradiotherapy followed by D2 gastrectomy was analyzed considering clinical and morphological findings. Twenty-four patients were treated with radiation therapy at a total dose of 45 Gy (daily dose was split into 2 fractions of 1 Gy and 1,5 Gy) concurrently with chemotherapy (2 cycles of xeloda at a dose of 1850 мg/ м2 given daily with a 12-hour interval and eloxatin, 100 мг/м2 given as an intravenous infusion every 3 weeks). Concurrent chemoradiotherapy was followed by a rest period, and then the control examination of the patients with the assessment of treatment results and surgery were performed. Detectable regression of both the primary tumor and regional metastases was observed in most patients. In accordance with G.A. Lavnikova classification, grade I pathological tumor response was found in 2 patients, grade II response in 6 patients, grade III response in 12 patients and grade IV response was observed in 4 patients. Thus, the treatment method was shown to be effective according to criteria of pathological tumor response. Our findings need to be confirmed by further clinical trials.